Virutalized Cloud Environment : A Survey (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud computing is one of today's most exciting technology because of its cost-reducing, flexibility, and scalability. With the fast growing of cloud computing technology, Data security becomes more and more important in it. In evaluating whether to move to cloud computing, it is important to compare benefits and also risks of it. Thus, security and other existed issues in the cloud cause cloud clients need more time to think about moving to cloud environments. But Security-related topics is one of the most arguable issues in the cloud computing which caused several enterprises looks to this technology uncertainly and move toward it warily[2]. A Virtualization Security framework is presented which contains two parts: virtual system security and virtualization security management.[1] The paper is devoted to the mechanism of monitoring of virtual machines aimed at guaranteeing increased security to cloud resources. Furthermore, the requirements for this mechanism are enumerated.[3]